Head and thorax elevation during cardiopulmonary resuscitation using circulatory adjuncts is associated with improved survival. (October 2022) - Moore, Johanna C.; Pepe, Paul E; Scheppke, Kenneth A.; Lick, Charles; Duval, Sue; Holley, Joseph; Salverda, Bayert; Jacobs, Michael; Nystrom, Paul; Quinn, Ryan; Adams, Paul J.; Hutchison, Mack; et al.
Abstract: Background: Survival after out-of-hospital cardiac arrest (OHCA) remains poor. A physiologically distinct cardiopulmonary resuscitation (CPR) strategy consisting of (1) active compression-decompression CPR and/or automated CPR, (2) an impedance threshold device, and (3) automated controlled elevation of the head and thorax (ACE) has been shown to improve neurological survival significantly versus conventional (C) CPR in animal models. This resuscitation device combination, termed ACE-CPR, is now used clinically. Objectives: To assess the probability of OHCA survival to hospital discharge after ACE-CPR versus C-CPR. Methods: As part of a prospective registry study, 227 ACE-CPR OHCA patients were enrolled 04/2019–07/2020 from 6 pre-hospital systems in the United States. Individual C-CPR patient data (n = 5196) were obtained from three large published OHCA randomized controlled trials from high-performing pre-hospital systems. The primary study outcome was survival to hospital discharge. Secondary endpoints included return of spontaneous circulation (ROSC) and favorable neurological survival. Propensity-score matching with a 1:4 ratio was performed to account for imbalances in baseline characteristics. Results: Irrespective of initial rhythm, ACE-CPR (n = 222) was associated with higher adjusted odds ratios (OR) of survival to hospital discharge relative to C-CPR (n = 860), when initiated in <11 min (3.28, 95 % confidence interval [CI], 1.55–6.92) and < 18 min (1.88, 95 % CI, 1.03–3.44) after the emergency call, respectively. Rapid use of ACE-CPR was also associated with higher probabilities of ROSC and favorable neurological survival. Conclusions: Compared with C-CPR controls, rapid initiation of ACE-CPR was associated with a higher likelihood of survival to hospital discharge after OHCA.